Elimination of measles by 2024: achievements and challenges (IMC Journal of Medical Science, 2020)
Measles is an infectious agent of viral origin with exceedingly high rate of transmissibility contributing to very high morbidity and mortality rates especially among children. Although measles is extremely infectious, control strategies of this virus used to be recognized as one of the most successful public health interventions ever undertaken. However, despite being vaccine-preventable disease measles has encountered an enormous resurgence as the rate of measles vaccination has declined and in many countries vaccination targets remain unmet and measles continues to claim hundreds of thousands of lives each year. This review discusses the reasons of the re-emergence of measles, the present global and Bangladesh situation and strategies that have been undertaken to combat this killer disease to eliminate measles globally by the year 2024.Ibrahim Med. Coll. J. 2020; 14(1): 53-58